ANALISIS USER EXPERIENCE DAN PERBAIKAN ANTARMUKA PENGGUNA WEBSITE BRI CERIA DENGAN MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) DAN CARD SORTING - Arji Surya Maulana, (2022)
CERIA is a product of PT. Bank Rakyat Indonesia, which was published in 2019. BRI CERIA maximizes the function of the website to offer and provide information about applications at CERIA. The CERIA website is currently no longer being developed, so it needs improvement. CERIA Interface Improvement uses a User Centerted Design approach that is indeed user-centred on the web site for developers, newbies. and Card Sorting is done to determine the information architecture on the website. Data obtained by the System Usability Scale method as many as 50 respondents. The BRI CERIA website has the aim of conveying information that is in line with what is in the application as well as a promotional medium. But over time, it needs to be done to the level of usability on the web so that the purpose of creating a website is met. In the process, the researcher uses User Centered Design (UCD) as the method applied. The application of the UCD method is carried out by carrying out questionnaires, card sorting and prototyping which is also combined with measurement of the System Usability Scale level. In this study, the usability value increased by 65% and resulted in the form of a website that is expected to be used as an improvement.